High-performance polyacrylonitrile-based pre-oxidized fibers fabricated through strategy with chemical pretreatment, layer-by-layer assembly, and stabilization techniques. (February 2021) - Sun, Xiaolu; Li, Songqi; Du, Mingyue; Huang, Fenglin; Zhang, Weidong; Wei, Qufu; Cai, Yibing
Novel high-performance polyacrylonitrile (PAN)-based pre-oxidized fibers (i.e. OPFHA-MEA-L ) with improved thermal stability and flame-retardant and mechanical properties were designed and made from the pristine PAN fibers through chemical pretreatment with hydroxylamine hydrochloride (HA) and monoethanolamine (MEA) aqueous solutions, then coated with chitosan (CS) and sodium tripolyphosphate (STPP) via layer-by-layer (LbL) assembly, and finally followed by stabilization in the air. The morphological structure, flammability, and thermal and mechanical properties of fabricated OPFs were systemically investigated. The results indicated that the PAN fibers after chemical pretreatment with HA and MEA had a large amount of hydrophilic groups. It would facilitate the increase of pre-oxidation degree for PAN fibers during stabilization and the deposition of positively and negatively charged CS-STPP flame-retardant coating. The fabricated OPFs (i.e. OPFHA-MEA-10 ) demonstrated superior comprehensive properties with charred residue of about 68.2%, breaking strength of about 295.1 N, breaking elongation of 12.6%, and limiting oxygen index value of about 41.5%, respectively, contributing to the improved thermal stability and flame-retardant and mechanical properties. It is envisioned that this innovative type of high-performance OPFs could be utilized for potential applications as flame retardant and in high temperature filtration.